2011
DOI: 10.1007/s11999-011-1869-z
|View full text |Cite
|
Sign up to set email alerts
|

Cartilage Matrix Formation by Bovine Mesenchymal Stem Cells in Three-dimensional Culture Is Age-dependent

Abstract: Background Cartilage degeneration is common in the aged, and aged chondrocytes are inferior to juvenile chondrocytes in producing cartilage-specific extracellular matrix. Mesenchymal stem cells (MSCs) are an alternative cell type that can differentiate toward the chondrocyte phenotype. Aging may influence MSC chondrogenesis but remains less well studied, particularly in the bovine system. Questions/purposes The objectives of this study were (1) to confirm age-related changes in bovine articular cartilage, esta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
46
1
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 55 publications
(52 citation statements)
references
References 47 publications
4
46
1
1
Order By: Relevance
“…Our group has previously shown that increased age decreases the chondrogenic potential of bovine MSCs. 47 Increased age has also been shown to reduce the chondrogenic potential of human MSCs. 48 Recent studies have shown that allogeneic MSCs can be used in humans without increased complication rates, and some companies have marketed allogeneic juvenile chondrocytes for cartilage repair (DeNovo Ò ; Zimmer, Inc.).…”
Section: Discussionmentioning
confidence: 99%
“…Our group has previously shown that increased age decreases the chondrogenic potential of bovine MSCs. 47 Increased age has also been shown to reduce the chondrogenic potential of human MSCs. 48 Recent studies have shown that allogeneic MSCs can be used in humans without increased complication rates, and some companies have marketed allogeneic juvenile chondrocytes for cartilage repair (DeNovo Ò ; Zimmer, Inc.).…”
Section: Discussionmentioning
confidence: 99%
“…They are composed of adipocytes and adipose connective tissue containing collagen and glycosaminoglycans. Its surface is covered with synovial membrane and its role is to facilitate the distribution of synovial fl uid within the joint and act as a cushion protecting exposed articular surfaces (Vahlensieck et al, 2002;Nakano et al, 2004).…”
Section: Authorsmentioning
confidence: 99%
“…At this age, such animals have not reached skeletal maturity. Chondrocytes from such tissue would probably be more adept at producing cartilage-specific ECM than chondrocytes obtained from an older donor, as seen in bovine 49,50 and human donors. 51 As with many tissue engineering studies, cells were expanded and differentiated in high glucose (25 mM) culture medium.…”
mentioning
confidence: 99%